Building the balanced scorecard using a structured approach hinged on identity and business framework. - Siriban-Manalang, Anna Bella D. (Philippine Industrial Engineering Journal)
This aim of this paper is to show the flow design of the structured approach and methodology proposed for the design of a balanced scorecard. It defines a sequential structured approach which starts from analyzing the entity with respect to its environment and multi-customer linkages in order to create a set of holistic integrative performance measures for the organization. It is applied to a system which services multiple client companies belonging to another industry. The process starts with the company recognizing its need for a performance measurement system that will show the status of strategies and goals achievement over time. Top management, in one of strategic planning sessions with the leaders of the company, through the assistance of this consultant, pinpointed the appropriateness of Kaplan and Norton's Balanced Scorecard approach to performance management. The paper progresses by transforming the qualitative measures in the initial design of the scorecard into quantitative indicators that can be monitored continuously. The study concludes by identifying the targets and weights for each indicator.